Study of the Potential of Lactobacillus rhamnosus A6 Isolated from Breast Milk as a Starter for Yoghurt Production - Paramita, Liya; Suparthana, I Putu; Arihantana, N.M. Indri Hapsari (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 4 No 2 (2017): Scientific Journal of Food Technology, 2017)
The aim of this research was to determine the potential of Lactobacillus rhamnosus A6 isolated from breast milk as a starter in the manufacture of yoghurt. The random design uses for the research with one factor treatment using different types of starter such as L. rhamnosus A6 as single starter, Streptococcus thermophilus and L. bulgaricus, L. rhamnosus A6 and L. bulgaricus, L. rhamnosus A6 and S. thermophilus, and L. rhamnosus A6 with S. thermophilus and L. bulgaricus. Milk was pasteurized at 80°C for 15 minutes and then added 6% starter culture according to the treatment. Each treatment was repeated 3 times to obtain 15 experimental units. The data obtained were analyzed by ANOVA and if there was any difference followed by Duncan test (DMRT). The best treatment was L. rhamnosus A6 with S. thermophilus and L. bulgaricus with good characteristic which content 3,16% protein; 3,74 x 106 CFU/ml total LAB; pH of 4,64; 0,53% total lactic acid; 408,3 mPas viscosity; color (white and like), aroma (acid and like), flavor (acid and like), texture (thick and like), and overall acceptance (like).